A Study on Hospitality Education at University : Jal’s Philosophy Education as an Example - Fujishima, Kiyohito (International Journal for Applied Information Management, 2021)
From the viewpoint of hospitality management, which has received particular attention in recent years, this paper considers it at the point of employee education. In recent years in Japan's industrial world, almost all fields are concerned about the importance of hospitality. Indeed, holding the 2020 Tokyo Olympic Games is spurring the momentum. Against this background, in this paper the author studied what kinds of education can be assumed for fostering qualities that can demonstrate hospitality, and examined measures to train hospitality minds in education conducted in university. As a reference example, the author introduced JAL's "Philosophy Education". It is based on the author's 30-year employee experience in JAL. JAL's thorough awareness reform analyzed the success stories of employees' minds to rebuild their hospitality mindset and to protect corporate reconstruction from major blows. The center of awareness reform of JAL is implementation of "Philosophy Education". "JAL Philosophy" is the result of the goal of how to raise awareness of customer priority that was originally low, from reflection on bankruptcy. It is made of a basic attitude as a human being and a way of thinking that should always be conscious of. As a result of this, employees of JAL became able to act with consciousness of this philosophy as the origin of all ideas. As a result, the foundation for customer first was solidly completed. From this case study, the author can see that "Philosophy" is the origin of ideas and actions. This can be utilized in the field of university. Before going to society, consider philosophy as the source of their own actions and repeat consciousness in everyday life. When participating in seminars and outside-campus training, they put on the habit of acting based on their own philosophy. By doing this, their motto is reflected in how they contact people and when they act. Having one firm motto will allow them to become aware of themselves as a society and be able to move smoothly to society. Many young people like this can build society by performing their full hospitality and mind.